Walking, body mass index, and self-rated health in a representative sample of Spanish adults - Vicente Romo-Perez; Dilia Souto; Jorge Mota (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract Obesity and physical inactivity (PI) are risk factors for chronic diseases and are associated with lifestyle and environmental factors. The study tested the association between PI, body mass index (BMI), and self-rated health in a representative sample of the Spanish adult population (N = 21,486). The sample included 41.5% men, with mean age 52.3 years (± 18.03), and age range 20-82 years. Prevalence of overweight/obesity was 34.2%/12.7% in women and 52.1%/12.7% in men (p < 0.001 for obesity in both sexes). 53% of women and 57.5% of men met recommended levels of physical activity by walking (≥ 150 minutes/week). According to logistic regression analysis, individuals that walked less had higher risk of overweight or obesity. Data from the population-based surveillance study support suggestions that regular walking by adults is associated with positive self-rated health and better BMI profile. Obesity and low/very low self-rated health have low prevalence rates to meet the recommendations.